Handbook of research on smart territories and entrepreneurial ecosystems for social innovation and sustainable growth - Palma-Ruiz, Jesus Manuel, 1978-; Sáiz Álvarez, José Manuel; Herrero-Crespo, Ángel (Advances in business strategy and competitive advantage., 2020)
"This book explores smart specialization strategy as an exportable model for improving competitiveness in different environments"--